(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Background: It was hypothesized that vestibular stimulation causes improvement in auditory and visual reaction time in young adults.Objective: The present study was undertaken to observe the effectiveness of 8 weeks of vestibular exercises on auditory and visual reaction time in young adults.Materials and methods: A total of 40 male and female young adults were part of the study after obtaining informed consent. They were grouped into control and intervention groups by random numbers generated by the software randomizer.org. Reaction time was recorded by the reaction time apparatus. Post-intervention values were recorded after 8 weeks of intervention and compared.Results: There was a significant improvement in the auditory and visual reaction times in young adults who followed by the intervention. Conclusion: The present study results suggest that vestibular exercises have a positive impact on reaction time. The study highlights the need for further detailed studies in this area.